The Changes in Hydration Status and Blood Glucose Levels of Young Football Athletes Who were Given Chia Seeds (Salvia hispanica, L.) Based Sports Energy Gel - Lestari, Yanesti Nur Avianda; Farida, Eko; Candra, Adiska Rani Ditya; Amin, Nur; Fauzi, Nur (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2024)
An athlete's hydration status is greatly affected by the adequacy of fluids and electrolytes during a workout. This study aimed to formulate a chia seed-based sports drink and analyzed its effect on hydration status and changes in blood glucose levels in football athletes. This experimental study on 46 young football athletes from Tyrex Java Semarang club was selected using a simple random sampling method. There are P(0)=control group (given 300mL placebo); and P(1)=treatment group (given 300 mL chia seed's sport energy gel). Administering placebo and treatment are done 45 minutes before exercise. Bodyweight and blood sugar level measurements are done 30 minutes before exercise and at 120 minutes. There were significant differences in the hydration status of study subjects before and after exercise (p=0.022), but the blood glucose level was not significant (p=0.413). However, the blood glucose level appeared to differ significantly (p=0.0001) between the control and treatment groups. As for changes in hydration status (kg and %) between the control group and treatment showed no sig-nificant differences (p=0.807 and 0.771). The conclusion is that giving chia seed's sports energy drink before exercise can maintain the blood glucose levels even though it does not impact the hydration status of athletes.